2022
DOI: 10.1186/s12871-022-01855-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the reliability of the upper lip bite test and the modified mallampati test in predicting difficult intubation under direct laryngoscopy in apparently normal patients: a prospective observational clinical study

Abstract: Background and aims Difficult endotracheal intubation is one of the most challenging operations in anesthesia. How to better predict difficult airway and make corresponding preparations to reduce the occurrence of accidents is a difficult task faced by anesthesiologists every day. This study decide to evaluate the value of the Upper Lip Bite Test (ULBT) and the Modified Mallampati Test (MMT) in predicting difficult intubation under direct laryngoscopy and find out the most intuitive and simple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
3
5
0
Order By: Relevance
“…When compared with the commonly used mouth opening test, it was found that the ULBT was inferior in predicting both difficult intubation and difficult laryngoscopy. This result is similar to previous results 14 , 15 , 27 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…When compared with the commonly used mouth opening test, it was found that the ULBT was inferior in predicting both difficult intubation and difficult laryngoscopy. This result is similar to previous results 14 , 15 , 27 .…”
Section: Discussionsupporting
confidence: 93%
“…For Youden's index, sensitivity and specificity are both considered. Previous studies 15 , 27 showed that the Youden’s index was optimal when grade 2 was used as the threshold, which is similar to present data, but the specificity was low in this situation.…”
Section: Discussionsupporting
confidence: 91%
“…Oral endotracheal intubation is the main method used to establish an artificial airway and a major means of emergency rescue. [20][21][22] Laryngoscopy is key to endotracheal intubation. Since the 19 th century, direct laryngoscopy has been widely used in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperatively, routine airway assessment was done by the main anaesthesiologist using the modified Mallampati classification,[ 11 ] thyromental distance, mouth opening and range of neck mobility. In the holding area, a blood sample was taken for baseline serum cortisol and blood glucose levels, and baseline SBP and heart rate were measured and recorded before starting nebulisation with either lignocaine or 0.9% NaCl according to patient allocation in the study groups.…”
Section: Methodsmentioning
confidence: 99%